DETERMINAN KINERJA KEUANGAN PERBANKAN SYARIAH PERIODE 2014-2018 - Pangesti, Kinanti Pradita; Sutanto, Himawan Arif (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jawa Tengah, 2020)
The increasing trend in the halal industry is one of the growth factors of sharia banking, but the increase in sharia banking growth is also accompanied by an increase in financing issued by sharia banks that can affect the financial performance of sharia banks. The high risk of financing and the weak fulfillment of the quality of Islamic bank human resources resulted in the performance of Islamic banks always below conventional banks. This study aims to determine the effect of intellectual capital, non-performance financing, Islamic social reporting and Islamic performance index on the financial performance of Islamic banking. The data was taken purposively from Islamic banking companies registered with the Financial Services Authority (OJK) for the 2014-2018 period. Multiple linear regression analysis has been used to analyze the data in this study. The results showed that Non-Permofance Financing (NPF) had a negative effect on the financial performance of Islamic Banks. Whereas Intellectual Capital as measured by Value Added Intellectual Coefficient (VAIC), Islamic Social Reporting, and Islamicity Performance Index has no effect on Islamic bank finance. .